Health emergency preparedness: an assessment of primary schools in Abakaliki, South-Eastern Nigeria - Ezeonu, Chinonyelum Thecla; Okike, Clifford Onuorah; Anyansi, Maria Nwakaego; Ojukwu, James Osaeloka (International Journal Of Community Medicine And Public Health, 2017)
Background: Children spend a significant proportion of their day in school, thus pediatric emergencies such as exacerbation of medical conditions, accidental and intentional injuries are likely to occur. An estimate of 10 -25% of injuries occur while the children are at school. It is the legal responsibility of the schools to ensure the safety and well-being of the pupils/students and staff during school hours working towards prevention of accidents and being prepared for immediate solutions when the accidents occur. Methods: A cross sectional descriptive study of 31 registered primary schools in Abakaliki Metropolis. A prepared check list of facilities necessary for emergency care at schools derived from the school health programme evaluation scale was used for the assessment. Data was analyzed using the SPSS statistical package version 8, comparing findings in public schools with the private schools using Chi square. The level of significance was set at p<0.05. Results: A health room was available in 9.7% of schools exclusively private schools. Nurses, doctors and trained first aiders were found in 6.5%, 9.7% and 32.3% respectively of schools. First aid boxes were available in 80.6% of the schools but only 67.7% of the schools could offer first aid treatment at emergencies. None of the public schools had a school safety patrol or a fire extinguisher in contrast to the private schools. Conclusions: Schools, especially the public schools in Abakaliki metropolis are ill prepared for emergencies.